Measuring Customer Satisfaction on the Quality of Financial Services in the most Populous Cities of the Oaxacan Isthmus Interoceanic Corridor - Cruz Celis, Felipe de Jesús; Utrera Garrido, Georgina; Cantú González, José Roberto (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To evaluate the level of customer satisfaction with respect to the quality of financial services offered in the five most populated cities of the Oaxacan Isthmus Interoceanic Corridor. MATERIAL AND METHOD: The methodology used to measure the quality of service is the Service Performance Model (SERVPERF) proposed by Cronin and Taylor (1992) designed to capture the client’s perception of the performance of the service received. A standardized questionnaire composed of 12 items was used; a total of 920 surveys were applied to the populations of Ciudad Ixtepec, Juchitán, Tehuantepec, Salina Cruz and Matías Romero. For the analysis of the information, descriptive statistics were used in the SPSS-21 statistical program. RESULTS: The derivations obtained show the following levels of approval per element: 69.07% for the tangible element, 56.57% for the reliability element, 53.47% for responsiveness, 59.24% for safety and 52.65% for empathy. CONCLUSIONS: The findings obtained from the average evaluation of the five most populated cities of the Oaxacan Isthmus Interoceanic Corridor indicate that 58.20% of the respondents, are satisfied with the quality of the financial services received.